Interleukin-13 promotes cellular senescence through inducing mitochondrial dysfunction in IgG4-related sialadenitis - Mengqi Zhu; Sainan Min; Xiangdi Mao; Yuan Zhou; Yan Zhang; Wei Li; Li Li; Liling Wu; Xin Cong; Guangyan Yu (Nature Publishing Group, 2022)
Abstract Immunoglobulin G4-related sialadenitis (IgG4-RS) is an immune-mediated fibro-inflammatory disease and the pathogenesis is still not fully understood. The aim of this study was to explore the role and mechanism of interleukin-13 (IL-13) in the cellular senescence during the progress of IgG4-RS. We found that the expression of IL-13 and IL-13 receptor α1 (IL-13Rα1) as well as the number of senescent cells were significantly higher in the submandibular glands (SMGs) of IgG4-RS patients. IL-13 directly induced senescence as shown by the elevated activity of senescence-associated β-galactosidase (SA-β-gal), the decreased cell proliferation, and the upregulation of senescence markers (p53 and p16) and senescence-associated secretory phenotype (SASP) factors (IL-1β and IL-6) in SMG-C6 cells. Mechanistically, IL-13 increased the level of phosphorylated signal transducer and activator of transcription 6 (p-STAT6) and mitochondrial-reactive oxygen species (mtROS), while decreased the mitochondrial membrane potential, ATP level, and the expression and activity of superoxide dismutase 2 (SOD2). Notably, the IL-13-induced cellular senescence and mitochondrial dysfunction could be inhibited by pretreatment with either STAT6 inhibitor AS1517499 or mitochondria-targeted ROS scavenger MitoTEMPO. Moreover, IL-13 increased the interaction between p-STAT6 and cAMP-response element binding protein (CREB)-binding protein (CBP) and decreased the transcriptional activity of CREB on SOD2. Taken together, our findings revealed a critical role of IL-13 in the induction of salivary gland epithelial cell senescence through the elevated mitochondrial oxidative stress in a STAT6-CREB-SOD2-dependent pathway in IgG4-RS.